PENGARUH DRILL MENGOPER BOLA TERHADAP SHORT PASSING ACCURACY SEPAK BOLA PADA SSB RESPA JUNIOR U-15 SUNGAI PAGAR - Haris Rinaldi; Slamet Slamet; Aref Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : In this research Problem is a Junior Respa average ability in pass a ball player is still lacking, of whom pass the ball at close range (short pass) players are often inaccurate, menggelintir and passes the ball long distances (long pass) are often not accurate and not inflated properly. Hence this research aims to know the influence of the drill passes the ball against short passing accuracy on SSB Respa Junior Research Fence River is located in the grounds of SSB Respa Junior Fencing Kampar River. The sample in this research totalled 16 people which is the player's Junior U-Respa SSb 15 River fence. Furthermore the values obtained are compared with ttabel at level 0.05 significant with N-1 degrees of freedom (15) turns the value obtained was 1,753 this indicates that the value of thitung (2,333) > ttabel (1,753) can thus be It was concluded that the hypothesis stating there the influence of the drill passes the ball against short passing accuracy On SSB Respa Junior U-15 River fence. From the analysis can also be drawn the conclusion that there is an influence of the drill passes the ball against an increase in short-passing accuracy. The sample in this research totalled 16 people which is the player's Junior U-Respa SSb 15 River fence, an Instrument or a tool to perform the measurement results of the passing player against SSB Repatriation Junior U-15 is to do a skill test accuracy short passing. Key Words: Drill Passes The Ball, Passing Accuracy